The dynamics of China’s mutton price fluctuations under extreme events - Zheng, Xiong; Daud, Adrian; Rosli, Anita; Taasim, Shairil Izwan (Atlantis Press SARL, 2024)
The notion of price instability has garnered renewed interest because of ongoing swings in agricultural prices in nations like China. We investigate the root cause of price volatility in the mutton market in China. To this purpose, we develop a theoretical model to explain endogenous price changes in the Chinese mutton supply chain by using information from our fieldwork and estimates from unobserved component models. We use vector auto regressions and weekly data on sheep and mutton prices in China to derive hypotheses from our theoretical model that can be tested under conventional assumptions. Our empirical results are consistent with those of our theoretical model, and the evidence of endogenous dynamics in observed prices is resistant to different specifications and estimating techniques. We demonstrate with the aid of numerical simulations how empirically based parameterizations of our theoretical model can accurately represent the key elements of mutton price fluctuations in China. Our descriptive, empirical, and numerical studies have accumulated evidence that strongly supports the endogenous nature of price instability in China’s mutton supply chain.